IDT116 : Materials and construction of modelling / Faculty of Art and Design - UiTM, Faculty of Art and Design (Universiti Teknologi MARA (UiTM), 2023)
This course is designed to expose the students to the model making process. In the course of industrial design, students should learn and have the skills and creativity in 2 dimensional form and 3 dimensional form. This course level aims to develop skills in model making process using a variety of materials, hand fabrication techniques, machines and tools. It will give students the opportunity to strengthen the model making skills in producing products / prototypes effectively and confidently. This course also includes analysing the physical features of different techniques, different materials, machines and tools used. At the end of this course, students should be able and capable to produce the product/prototypes using variety of materials, hand fabrication techniques, machine and tools.